Predictive value of neutrophil to lymphocyte ratio for ischemic stroke in patients with atrial fibrillation: A meta-analysis - Lu, Ming; Zhang, Yeying; Liu, Rui; He, Xiaoming; Hou, Bonan (Frontiers in Neurology, 2022)
Objective Atrial fibrillation (AF) is an important risk factor for stroke, but the currently used CHA2DS2-VASc score has significant limitations in predicting the risk of stroke. It is important to find new biomarkers to predict stroke risk in patients with AF or as a complement to the CHA2DS2-VASc score. Neutrophil-to-lymphocyte ratio (NLR) may be of potential value. This systematic review and meta-analysis evaluated the association between NLR and stroke risk. Methods We searched in electronic databases such as PubMed and EMBASE. The final included studies were analyzed by Stata 12.0 software. Subgroup analyses were used to explore sources of heterogeneity. Publication bias was assessed by Egger's test and Begg's test. Sensitivity analyses assessed the stability of outcomes. Results A total of 11 studies with a total of 35,221 patients were included. NLR levels are associated with stroke risk in patients with atrial fibrillation (WMD = 0.72, 95%CI = 0.43–1.01). There was a correlation between the occurrence of stroke and NLR level in AF patients (WMD = 1.96, 95%CI = 1.38–2.53). The incidence of stroke was significantly higher in patients with atrial fibrillation with NLR ≥3 than in those with NLR <3 (RR = 1.4, 95%CI = 1.24–1.58). Conclusion This study shows that high NLR values are associated with a higher risk of stroke in AF patients. The incidence of stroke in AF patients with NLR ≥3 was 1.4 times higher than that with NLR <3 (p < 0.001). NLR may be considered as a complementary risk assessment for CHA2DS2-VASc score, especially for AF patients with CHA2DS2-VASc score <2. NLR may be a potential biomarker for predicting stroke risk in patients with AF.